Ferromagnetic order in dipolar systems with anisotropy: application to magnetic nanoparticle supracrystals - Russier, V.; Ngo, E. (Condensed Matter Physics, 2017)
Single domain magnetic nanoparticles (MNP) interacting through dipolar interactions (DDI) in addition to the magnetocrystalline energy may present a low temperature ferromagnetic (SFM) or spin glass (SSG) phase according to the underlying structure and the degree of order of the assembly. We study, from Monte Carlo simulations in the framework of the effective one-spin or macrospin models, the case of a monodisperse assembly of single domain MNP fixed on the sites of a perfect lattice with fcc symmetry and randomly distributed easy axes. We limit ourselves to the case of a low anisotropy, namely the onset of the disappearance of the dipolar long-range ferromagnetic (FM) phase obtained in the absence of anisotropy due to the disorder introduced by the latter.